THE STUDENT'S PERCEPTION TOWARDS ENGLISH SPEAKS UP CLUB TO IMPROVE SPEAKING SKILL - Widuri Indah Dwi Jayanti; Maya Ulyani; Ani Susanti (Premise: Journal of English Education and Applied Linguistics, 2022)
Speaking is a complicating skill for students to master, since they must master all of its components such as grammar, vocabulary, fluency, comprehension, and pronunciation. As a result, most EFL students struggle to succeed. The purpose of this study is to identify whether or not the speaking club helps students improve their speaking skills. The subjects of this study were the students who joined the Sixta Speaks Up as an English-speaking club in the Vocational High School by a group of forty students. The qualitative descriptive research design was adopted in this study. The author employed questionnaires delivered to students through a Google form to gather information. According to the findings of this study, the majority of students who participate in speaking clubs make significant improvements in their English speaking skills, including enhancements in pronunciation, vocabulary, and fluency in speaking English in general. The speaking activities also increase their confidence to exchange their ideas.